Big Data Concepts and Techniques in Data Processing - Suvarnamukhi, B; Seshashayee, M (International Journal of Computer Sciences and Engineering, 2025)
In digital world where data grows rapidly because of more use of internet and number of devices like, smart phones, laptops, personal and machines at a very increase rate. Big data is a pool of large amounts of data collected from various sources, such as social working sites like facebook and transactional data like online shopping sites. Big data is stored in distributed architecture framework. Hadoop is an open source framework for creating distributed applications that process huge amount of data. Hadoop keeps them all together under a single roof with their functionalities. Preparing of information can incorporate different activities like highlighting, indexing and searching. It is highly difficult to process in single machine, with huge amount of data. This paper focused on Concepts and Techniques in Big Data processing